STUDI MEDIA DAN BUDAYA POPULER DALAM PERSPEKTIF MODERNISME DAN POSTMODERNISME - Muh. Hanif (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2011)
Initially media studies is started because of the emergence mass media in 1920-1930s.In the beginning media studies focus on media it self, in the following development in 1970smedia studies is enlarged study toward the culture of the audiences who used media massa.There are different opinion between modernism and postmodernism as follows: firstly,in the philosophical aspect including epistemology, metaphysic, and the nature of human;modernism stresses on objectivity, realism and autonomy; on the contrary postmodernismstresses on subjectivity, and social construction. Secondly, in the aspect of media studiesincluding the existence of mass media, news, journalist, ethics and values; modernism stresseson objectivity, however postmodernism stresses on subjectivity.Popular culture is constructed by mass media on behalf the interest of capitalists whooffer and trade various needs and manipulative desires in the advertisement by using symbolsto provoke members of societies to buy more and more continuously. Because of hegemony,members of societies as mass media users without consciousness they are becomeconsumptive, hedonistic, and having false consciousness. We need critical consciousnessbased on postmodernism point of view about the subjectivity of mass media. To broaden anddistribute critical consciousness, we can perform media literate training for media users sothey can use mass media smartly and wisely.